Karakterisasi Penampilan Agronomi Beberapa Varietas Bawang Merah (Allium ascalonicum L.) Akibat Perbedaan Konsentrasi Gibberellic Acid (GA3) di Dataran Rendah Kabupaten Karawang - Septiani, Gina Tri; Azizah, Elia; Supriadi, Devie Rienzani (UNIVERSITAS LABUHANBATU, 2023)
Shallot production in Karawang Regency has decreased every year. Efforts to increase shallot production can be carried out by administering growth regulators Gibberellic Acid (GA3) and superior seeds. The purpose of this research was to obtain the right concentration of Gibberellic Acid (GA3) to be applied to several shallot varieties in the lowlands of Karawang Regency. The study used an experimental method with a factorial Randomized Block Design (RBD) consisting of 2 factors. The first factor was the varieties (S) consisting of 3 levels (Batu, Bauji, Maja) and the second factor was the concentration of GA3 (G) consisting of 4 levels (0 ppm, 100 ppm, 150 ppm, 200 ppm), each treatment was repeated 3 times so that There are 36 experimental units. The data obtained were analyzed using the F test and further tested with the DMRT (Duncan Multiple Range Test) level of 5%. The results showed that there was no interaction between several shallot varieties with different concentrations of Gibberellic Acid (GA3) on the parameters of the number of tillers, the weight of dry tubers per clump, and the weight of dry stover tubers, but there were independent varieties factors that had a significant effect on each observation parameter.Â Keywords : Growth Regulatory Substances, Dry Tuber Weight, Shallot Production